Electrospun nanofibers of poly(vinyl alcohol) and chitosan-based emulsions functionalized with cabreuva essential oil - Lamarra, Javier Andres (2020)
Among the essential oils (EOs), the cabreuva essential oil extracted from the wood of Myrocarpus fastigiatus, is a promising compound for potential applications in the field of pharmaceuticals and food packaging. To overcome the low solubility of cabreuva EO and to protect it, a two-step process, emulsion formation compound by chitosan, SDS, and PVA, and subsequent ionic crosslinking with sodium citrate, was proposed. The formulation containing 0.75% of chitosan and 1% of SDS proved to be the most stable. An alternative to produce nanostructures and encapsulate the EO is the fiber formation through the electrospinning method. The system composed by a PVA solution assembled with crosslinked emulsions modified the viscosity, influencing the morphology of the obtained nanofibers. The advantage of the electrospun nanofibers was their ability to be an effective carrier of the cabreuva EO and the capacity of controlling the compound release that proved an effective activity against broad spectra of micro-organisms (Candida albicans, E. coli, S. aureus, and S. epidermidis). The Gallagher-Corrigan model, used to fit the release profiles of matrices in contact with increasing ethanol proportion from 25:75 to 50:50 showed higher Kb in relation to k suggesting that the polymer swelling played an increasingly prominent role in the EO delivery. The developed nanostructures would be materials with potential applications in the biomedical field.